Thermal proprieties and decomposition kinetics of asphalt binder modified by thermoplastic polymer and nanoclay Dellite 43B - Lucas Tamele Jr.; Herminio Muiambo; Giovanna Buonocore; Carlos Cumbane (Journal of Applied Science and Engineering, 2022)
Asphalt is the most suitable material for road pavement. However, due to mechanical and environmental loads, asphalt tends to show fatigue damage and thermal cracking. To avoid or mitigate these failures, the present research proposes the use of thermoplastic polymers, High-density polyethylene (HDPE) and Linear low-density polyethylene (LLDPE), and nanoclay Dellite 43B for asphalt binder modification. The nanocomposites were prepared in a high-shear mixer using the solution intercalation method for a mixing time of 1.5 h, at 180oC and 5000 rpm. Thermogravimetric analysis (TGA) was performed with a heating rate of 10 oC/min, from 25 to 600 oC under air and N2 atmospheres with a flow rate of 100 mL/min. The TGA data and kinetic analysis showed that the nanocomposites presented greater thermal stability than unmodified asphalt and polymer-modified asphalt binder. Hence, the initial and final decomposition temperatures were increased and the incorporation of nanoclay lead to higher activation energy, entropy, enthalpy change and Gibbs free energy values.